2017
DOI: 10.2501/ijmr-2017-052
|View full text |Cite
|
Sign up to set email alerts
|

Odour-induced Taste Enhancement and Consumption of Low-sugar Pastry

Abstract: This paper describes a study that tests for the enhancement of low-sugar pastry via olfaction and examines its effects on pastry consumption. Olfactory taste enhancement preserves the nutritional benefits of low-sugar pastry while retaining the pleasure of full-sugar pastry. Willingness to reduce sugar intake and eat healthily is stronger today than at any time before in western societies, and low-sugar pastry can be effective in reducing sugar intake among consumers in these markets. The challenge, however, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
5
0
4
Order By: Relevance
“…Vanillin, which is an odorous extract of vanilla, is a sugar-congruent odor and used as such in sensory marketing research in Western countries including in France (Spence, 2015; Thai et al , 2011). Vanillin is a sweet taste-congruent olfactory input was confirmed in a study by Koubaa (2017), who found strong associations between vanillin and sweetness ratings from experimental data gathered in France.…”
Section: Materials and Experimentsmentioning
confidence: 70%
See 2 more Smart Citations
“…Vanillin, which is an odorous extract of vanilla, is a sugar-congruent odor and used as such in sensory marketing research in Western countries including in France (Spence, 2015; Thai et al , 2011). Vanillin is a sweet taste-congruent olfactory input was confirmed in a study by Koubaa (2017), who found strong associations between vanillin and sweetness ratings from experimental data gathered in France.…”
Section: Materials and Experimentsmentioning
confidence: 70%
“…Similar findings were also reported by Schifferstein and Verlegh (1996) for liquid items. Other odors such as chocolate and cinnamon are found to enhance sweetness perception and boost consumption of pastry (Biswas et al , 2014; Krishna, 2012; Koubaa, 2017). This finding was also significant for pairings of salty odors and saltiness levels (Nasri et al , 2011).…”
Section: Odor-taste Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two gustatory stimuli were sucrose (T1: sweet taste) and salt (T2: salty/savoury taste). These odour and taste stimuli had been demonstrated in previous research to be associated with perception of sweet and savoury foods [63,64].…”
Section: Sensory Experiments 231 Stimulimentioning
confidence: 62%
“…En effet, il a été démontré que la stimulation olfactive intensifie le goût à deux conditions: (1) que l'odeur sentie soit congruente avec le goût attendu et (2) que le goût soit gustativement perceptible avant l'intervention de la stimulation olfactive (Meierhenrich et al, 2005). En l'absence de la condition de congruence, l'effet intensificateur est partiellement ou totalement anéanti (Krishna et al, 2014), et si le goût n'est pas perceptible gustativement avant l'intervention de la stimulation olfactive, cette dernière ne peut pas l'engendrer (Koubaa, 2017). Or, dans le cas de produits diététiques, on peut s'attendre à ce que la stimulation olfactive soit peu efficace dans l'influence de la perception de goût étant donné que les produits diététiques sont pauvres en ingrédients gustatifs qui sont les stimuli réels du goût.…”
Section: Introductionunclassified